The implementation of the use of electronic information technologies in pre-trial proceedings - Kabykeshovna N. A., Kuzhabayeva G. M., Umetov A. U., Birzhanov K. K, Maymakova A. B., (Opción, 2019)
This article is aimed at studying the current state and justification of the need for the use of electronic information technologies by the Internal Affairs agencies in the course of pre-trial criminal proceedings in the Republic of Kazakhstan via the analysis of theoretical and regulatory legal sources and the study of statistical information. In result, the increased use of electronic technology will make it possible to provide electronic criminal proceedings evidencing, thereby modernizing the entire criminal justice system. In conclusion, creation and use of mobile computer systems for officials engaged in pre-trial investigation, to work on-site and specialized forensic systems.